The Organ of Santa Catarina's Church, Calheta, S. Jorge Island - Azores - Luís Henriques (2017)
The organ of Santa Catarina's church in Calheta, São Jorge Island was build by the Portuguese eighteenth-century organ-builder António Xavier Machado e Cerveira in 1790. The instrument was purchased for this church after being rejected by the nuns of a convent in Ponta Delgada. It was restored by master organ-builder Dinarte Machado in 1991.